2016
DOI: 10.1037/tra0000098
|View full text |Cite
|
Sign up to set email alerts
|

Multiple trauma exposure and psychosocial functioning in Singaporean children in out-of-home care.

Abstract: Findings highlight the importance of conducting comprehensive assessments of children in out-of-home care to provide specialized interventions for children with interpersonal trauma exposure. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The algorithm takes into consideration an individual's needs from a wide range of domains. Details of the Singapore version CANS tool have been previously described (Liu et al, 2016). The tool consists of seven domains (i.e., life functioning, school, child behavioral and emotional problem, trauma, child risk behavior, strengths, and caregiver).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The algorithm takes into consideration an individual's needs from a wide range of domains. Details of the Singapore version CANS tool have been previously described (Liu et al, 2016). The tool consists of seven domains (i.e., life functioning, school, child behavioral and emotional problem, trauma, child risk behavior, strengths, and caregiver).…”
Section: Methodsmentioning
confidence: 99%
“…These ratings indicated different actions ranging from 0 (no evidence of a need and no need for action), 1 (mild degree of need and the need for monitoring or prevention), 2 (moderate need which requires action), to 3 (severe need requiring immediate or intensive action). Ratings of 0 and 1 were classified as nonactionable needs, whereas ratings of 2 and 3 were classified as actionable needs (Liu et al, 2016). The reliability of the Singapore CANS tool has been examined and previously reported (Liu et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of multiple trauma exposure of 721 Singapore children in out-of-home care revealed that 63% experienced at least one interpersonal trauma and 35% experienced multiple trauma exposure (Liu et al 2016). The children with multiple trauma exposure had poorer psychosocial functioning with higher number of lifefunctioning needs, behavioral and emotional needs, and risk behavior needs.…”
Section: Definitionsmentioning
confidence: 99%
“…Nevertheless, numerous studies have identified several barriers to academic performance of adolescents in residential care, including placement disruptions and mobility (Leloux-Opmeer et al, 2016). Multiple out-of-home placements can exacerbate trauma (Liu et al, 2016;Riebschlenger, Day, & Damashek, 2015) and can negatively impact an adolescent's school engagement and academic performances (see Perfect, Turley, Carlson, Yohanna, & Gilles, 2016, for a review). Notably, school mobility is another barrier (Jones, 2012).…”
Section: Residential Care: Education and Treatmentmentioning
confidence: 99%